The Medicalisation of Childhood Behaviour and the Rise of Attention Deficit Hyperactivity Disorder (ADHD) Diagnoses in Lagos State, Nigeria (Journal of Human Sciences, 2025)
Attention Deficit Hyperactivity Disorder (ADHD) is one of the most common neurodevelopmental disorders in children and teens worldwide. Children with ADHD struggle with concentration, conduct, and self-regulation.  As ADHD has increased in Nigeria, this research explores how children's conduct has been medicalised. Its objectives are to determine the incidence of ADHD diagnoses in Nigerian children and adolescents, examine their causes, assess their effects, and examine educators' and parents' responsibilities in the diagnosis process. Surveys were the main data collection method in this quantitative investigation. Two-stage purposive and snowball sampling was used to select 200 participants (100 parents and 100 educators) from five Lagos State LGAs: Ikeja, Lagos Island, Agege, Alimosho, and Amuwo-Odofin.  SPSS was used to create descriptive statistics (tables) and inferential statistics (correlation and regression analyses). The study found a somewhat positive association between awareness and early diagnosis, as well as a positive correlation between parental education and diagnosis; however, Western culture had no significant influence. The data show that parents are more involved in ADHD assessment.  This study supports the need to raise awareness about ADHD and educate medical professionals and educators. Cultural awareness and family education are essential for accurate ADHD diagnosis and effective therapy. Addressing these characteristics may enhance ADHD early detection, stigma reduction, and help in Nigeria.